Burden of chronic obstructive pulmonary disease in adults aged 70 years and older, 1990-2021: Findings from the Global Burden of Disease Study 2021. - Kaifang Meng; Xu Chen; Zhishang Chen; Jing Xu (PLoS ONE)
Background Life expectancy at age 70 has continued to rise globally over the past 30 years. However, a comprehensive assessment of the burden of COPD in older adults is lacking. We aimed to estimate the burden of COPD and its attributable risk factors among adults aged ≥70 years. Methods Data on the prevalence, incidence, deaths, disability-adjusted life years (DALYs), and risk factors of COPD among adults aged ≥70 years from 1990 to 2021 across 204 countries and territories, were sourced from the Global Burden of Disease Study 2021. Estimated annual percentage change (EAPC) was used to illustrate temporal trends at global and regional levels from 1990 to 2021. Results In 2021, the global numbers of prevalent and incident COPD cases among older adults were 99.7 and 7.4 million, increasing by 162.2% and 157.4% from 1990. The prevalence and incidence rates increased from 18823.5 (95% uncertainty interval (UI) 16324.4-21208.4) to 20165.6 (17703.8-22549.4) and 1429.0 (1224.2-1613.0) to 1502.7 (1309.0-1677.9) per 100,000 population (EAPC 0.31, 95% CI 0.28-0.33; 0.17, 95% CI 0.16-0.19). The global numbers of COPD-associated deaths and DALYs in 2021 reached 2.9 and 45.4 million, increasing by 70.7% and 70.0% from 2019, while the corresponding rates declined (both EAPC <0). The highest prevalence and the largest increase in incidence rate occurred in high sociodemographic index (SDI) regions, while the largest increase in death and DALY rates occurred in the low SDI regions. The United States had the highest prevalence rates in 2021, while Iran had the largest increase. From 1990 to 2021, the death rates attributable to ambient ozone pollution-related COPD in older adults have risen, particularly in low and low-middle SDI regions. Conclusion COPD in older adults has progressively become a global health challenge with rising prevalence and incidence rates. Although the death and DALY rates attributed to COPD have globally decreased in older adults, the absolute counts are rapidly increasing. The inequalities across different regions and countries underscore a multi-faceted approach to COPD management in older adults.